SUPPORTING STRATEGIES OF THE RECOVERY FOR STUDENTS' LITERACY AND NUMERACY IN ELEMENTARY SCHOOL ENVIRONMENT - M. Zainudin; Doni Abdul Fatah (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2022)
The purpose of this study was to obtain an overview of the classroom and school environment as a support for literacy and numeracy recovery. This quantitative descriptive research uses a survey method. The survey was conducted on teachers at SDN Pacing I and SDN Pacing II Sukosewu, Bojonegoro Regency. The data were obtained from the respondents (12 classroom teachers). Six teachers came from SDN Pacing I Sukosewu and six from SDN Pacing II Sukosewu. The instruments used in this study were a questionnaire about the text-rich classroom environment, the text-rich school environment, the numeracy-rich classroom environment, and the numeracy-rich school environment. The data analysis technique in this study used the percentage of answers. The results of this study show that improving strategies for supporting students' literacy and numeracy recovery can be carried out on indicators 1) the books in the library are grouped and arranged by genre, 2) the availability of at least 3 literacy corners and an environment that supports differentiated learning, 3) teachers have conducted research classroom actions related to student literacy, 4) teachers collaborate with other teachers to strengthen literacy in the co-curricular domain, 5) teachers collaborate with other teachers to strengthen literacy in extracurricular areas, 6) there are height/weight measuring devices, thermometers, numerical descriptions of space in the school environment, 7) classrooms are equipped with tools related to numeracy, 8) there is a word wall developed from the learning theme, 9) in the school environment there is a positive message that students can become numerates, and 10) the teacher provides an example in implementing numeracy.